Developmental patterns of ganglioside sialosylation coincident with neuritogenesis in cultured embryonic chick brain neurons. - Rosenberg, Abraham; Sauer, Anke; Noble, Ernest P.; Groß, Hans Jürgen; Chang, Ruth; Brossmer, Reinhard (The journal of biological chemistry, 1992)
Chick brain precursor neurons were observed to introduce sialic acid biosynthetically into only three specific gangliosides: monosialosyl lactosyl ceramide (GM3), disialosyl lactosyl ceramide (GD3), and disialosyl gangliotrihexosyl ceramide (GD2), when sialic acid was labeled metabolically by its obligate precursor, [3H] ManNAc. Sialosyl donor CMP-[3H]NeuAc supplied in the culture medium gave rise uniquely to surface-labeled GD3. Thus sialosyl transferase/GD3 synthase activity is expressed both intraneuronally and in the neuronal exofacial surface. Upon epidermal growth factor-induced onset of neurite outgrowth, labeled complex sialosyl gangliotetrahexosyl ceramide species of gangliosides began to appear in the embryonic neuronal plasma membrane. However, intraneuronal and exofacial sialosyl transferase/GD3 synthase activities remained constant, with or without neurite outgrowth. Moreover, simpler species of gangliosides maintained a steady quantitative sialosyl level (1.6 +/- 0.2 micrograms of sialic acid/mg of protein), whereas more complex species completely absent before neurite outgrowth accrued and reached 4.8 +/- 0.9 micrograms of sialic acid/mg of protein with full neurite development. This analysis of developmental patterns of ganglioside sialosylation has provided evidence that stable neurite outgrowth depends upon generation by the neuron of special plasma membrane with a massive content of complex higher species of gangliosides.
Artikel-Version: 4. Januar 2021
Gesehen am 24.06.2024